2021
DOI: 10.1016/j.cmi.2021.03.009
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of severe acute respiratory syndrome coronavirus 2 in Slovenia: results of two rounds of a nationwide population study on a probability-based sample, challenges and lessons learned

Abstract: Objectives Seroprevalence surveys provide crucial information on cumulative severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) exposure. This Slovenian nationwide population study is the first longitudinal 6-month serosurvey using probability-based samples across all age categories. Methods Each participant supplied two blood samples: 1316 samples in April 2020 (first round) and 1211 in October/November 2020 (second round). The first-round sera were tested usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 38 publications
0
10
0
Order By: Relevance
“…Internationally, Germany can be classified among the countries with low seroprevalence in 2020, similar to Norway (0.9%, November to December 2020) 32 , Denmark (2.0%, August to October) 33 , and, earlier, Iceland (0.3%, April to June) 34 . Somewhat higher seroprevalences were found in nationwide population studies in Slovenia (4.3%, mid-October to mid-November 2020) 35 , Spain (5.2%, April to June) 36,37 , the Netherlands (4.5%, June to August) 38 , and England (8.9%, November) 39 and a much higher seroprevalence of 28% in October-November was estimated for the Czech Republic 40 . In Norway, the estimated ratio between seroprevalence and cumulative incidence was 1.1 32 , the study from Iceland showed a ratio of 1.8 34 , and the Danish study a ratio of 6 in August and 3 in October and December 41 .…”
Section: Discussionmentioning
confidence: 83%
“…Internationally, Germany can be classified among the countries with low seroprevalence in 2020, similar to Norway (0.9%, November to December 2020) 32 , Denmark (2.0%, August to October) 33 , and, earlier, Iceland (0.3%, April to June) 34 . Somewhat higher seroprevalences were found in nationwide population studies in Slovenia (4.3%, mid-October to mid-November 2020) 35 , Spain (5.2%, April to June) 36,37 , the Netherlands (4.5%, June to August) 38 , and England (8.9%, November) 39 and a much higher seroprevalence of 28% in October-November was estimated for the Czech Republic 40 . In Norway, the estimated ratio between seroprevalence and cumulative incidence was 1.1 32 , the study from Iceland showed a ratio of 1.8 34 , and the Danish study a ratio of 6 in August and 3 in October and December 41 .…”
Section: Discussionmentioning
confidence: 83%
“…Significantly higher seropositivity was observed after the second pandemic peak, varying from 11.4% in Poland (October–November 2020) [ 21 ], and 19.3% in Spain (Madrid, at the end of 2020) [ 22 ], to 21.1% in Switzerland (Geneva, November–December 2020) [ 23 ]. In Slovenia, the seroprevalence after the first (April 2020) and second (October–November 2020) waves was found to be 2.78% and 4.06%, respectively [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…To assess the accuracy of the above approach, the estimated cumulative infection fractions were compared to 22 previously published nationwide seroprevalence surveys across 14 countries (Supplemental Table S1) (Alharbi et al, 2021;Anand et al, 2020;Bogogiannidou et al, 2020;Espenhain et al, 2021;Hallal et al, 2020;Le Vu et al, 2021;Merkely et al, 2020;Murhekar et al, , 2021Nah et al, 2021;Poljak et al, 2021;Pollán et al, 2020;Reicher et al, 2021;Snoeck et al, 2020;Ward et al, 2020). Only surveys attempting to estimate nationwide seroprevalence in the general population (in particular, either using geographically or demographically stratified sampling or adjusting for sample demographics) were included.…”
mentioning
confidence: 99%